Postcards to Hitler : a German Jew's defiance in a time of terror - Neuburger, Bruce 2013- (Monthly Review Press, 2024)
"Postcards to Hitler is the story of a Munich family living as close neighbors to the demagogue who will become the primordial commander of the Nazis-as passionately told by one of their surviving relatives, Bruce Neuburger. As the story begins, Europe has enjoyed many decades of peace on its own soil and Jews are enjoying a social renaissance in the industrializing, urbanizing rising star that is Germany. It is not at all clear that this good fortune might begin to unravel. Benno Neuburger, a modest German land investor from Munich, and Anna Einstein, daughter of a cattle dealer from Laupheim, marry in 1907. Their family life begins at a relatively prosperous moment in Germany - and a particularly optimistic time for German Jews. Even when news of an assassination in an "obscure" Balkan corner of the continent passes like a cold wind through Munich on a warm beer-garden July day in 1914, people shudder but feel no great alarm.^